(untitled) (Docentes 2.0 Journal, 2025)
Current teaching faces the challenge of incorporating innovative methods that foster motivation and learning. The purpose of this research was to determine the level of gamification use among university students. A study was conducted within the pragmatic paradigm, employing a systematic mixed-methods approach, a bibliographic documentary thematic narrative design, and a longitudinal design spanning 2020-2025. Twenty-two relevant studies were selected from data sources such as PubMed, Scopus, Web of Science, SciELO, and Google Scholar, using rigorous selection and exclusion criteria and applying the PRISMA guidelines to ensure the quality and reliability of the analysis. The results revealed positive acceptance and awareness of gamification; however, its effective implementation is constrained by a lack of teacher training, scarce resources, and an absence of pedagogical planning. Furthermore, only three studies evaluated the dynamics, mechanics, and components, showing mixed results. The discussion confirmed that gamification is a motivating and effective educational method, consistent with previous studies that highlight its potential and its challenges, stemming from limited student training and insufficient resources. Furthermore, it emphasizes the importance of contextualized and supervised designs to optimize its implementation. In conclusion, gamification has a significant educational impact, but achieving its effectiveness requires a supervised, structured implementation. It is recommended to explore its integration with emerging technologies and evaluate its long-term impacts on professional skills.